2021
DOI: 10.1039/d1fo01517f
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol supplementation alleviates nonalcoholic steatohepatitis and atherosclerosis in high-fat, high carbohydrate and high-cholesterol diet-fed rats

Abstract: Sesamol, a major ingredient in sesame seeds (sesamum indicum L.) and its oil, is considering as a powerful functional food ingredient. However, few researches investigated its effects on high-fat, high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Sesamol is extracted from sesame oil and can be used as an antioxidant in foods and medicines [ 44 ]. Several studies have revealed that sesamol protects the body from various disease conditions such as obesity, hyperlipidemia, and diabetic foot ulcer mainly through regulating lipid as well as energy metabolism and reducing inflammatory cell infiltration [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sesamol is extracted from sesame oil and can be used as an antioxidant in foods and medicines [ 44 ]. Several studies have revealed that sesamol protects the body from various disease conditions such as obesity, hyperlipidemia, and diabetic foot ulcer mainly through regulating lipid as well as energy metabolism and reducing inflammatory cell infiltration [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of sesamol as an add-on drug along with the available therapy to control hyperlipidemia and ischemic heart diseases [51]. Sesamol has been documented to posses Sesamol with crocin, an approach that could not only abolish the toxic effects of sesamol on platelets, but also enhance the quality of treatment due to their synergistic action, on the lines of combinatorial drug therapy [52].…”
Section: Combination Therapy Of Sesamol With Other Drugsmentioning
confidence: 99%
“…Cholesterol-rich diets induce systemic inflammation . High fat and cholesterol diets promote the development of atherosclerosis and steatohepatitis. , Many studies reported that high fat and cholesterol diets (HFCDs) disturbed the gut microbiome in various ways, such as reducing the alpha diversity of bacteria, decreasing the Firmicutes to Bacteroidota ratio, suppressing some probiotics (e.g., Akkermansia , Bifidobacterium , and Lactobacillus , ), or irritating the potentially harmful bacterial (e.g., Desulfovibrio , Desulfovibrionaceae , Oscillibacter , Alistipes , and Erysipelotrichaceae , ).…”
Section: Introductionmentioning
confidence: 99%